Penggunaan Model Pembelajaran Discovery Learning dalam Meningkatkan Partisipasi Siswa Kelas VIIIA SMPK Santo Stanislaus Surabaya Materi Sakramen Baptis - Lukas Lito Wato (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
Good education can improve the quality of both students and educators. The low level of student activity and participation in studying Catholic Religious Education material will indirectly affect the learning outcomes achieved. This article discusses the use of the Discovery Learning model to improve student participation in class VIIIA at SMPK Santo Stanislaus Surabaya in the Sacrament of Baptism material. The focus is on understanding the success of using the Discovery Learning method to increase student participation in class VIIIA at SMPK Santo Stanislaus Surabaya. The emphasis of this study is that the use of the Discovery Learning model can enhance student participation, which in turn impacts the achievement targets and academic performance of the students. The methods used in this study are tests and observations. The expected results are to help students further increase their participation in Catholic Religious Education lessons. This article contributes to enriching the practice of Catholic Religious Education and supports the vision and mission of education in Indonesia.